La construcción de un personaje histórico en el cómic: la Cleopatra de Martz Schmidt y Pérez Navarro - García Fleitas, María de la Luz (2022)
Este estudo analisa como um retrato estereotipado da rainha egípcia Cleópatra VII sobrevive na banda desenhada de Martz Schmidt e Pérez Navarro. A personagem baseia-se em antigas construções de identidades que, vindas da antiguidade clássica, perduram ao longo do tempo e se inserem num produto de massa como a banda desenhada: Cleópatra, a partir de uma relação dicotómica entre Ocidente e Oriente, é entendida como mera estrangeira; e, a partir de uma categorização heteropatriarcal, torna-se um objeto sexual, é fortemente hipersexualizada e é entendida como usurpadora do poder, constituindo um exemplo de como a identidade de género foi parcialmente construída na nossa cultura ocidental.
The current study aims to provide an analysis of the persistent duration of the stereotypical representation of the Egyptian queen Cleopatra VII as she is portrayed in the comic by Martz Schmidtand Pérez Navarro. Her characterization is based on ancient constructions of identity which, having originated in Classical Antiquity, have lasted over time and, as such, seem to have a place in mass products such as comics. These identities correspond to her depiction as merely a foreigner from the perspective of the dichotomy between Eastand West, whereas, corresponding to a hetero‐patriarchal categorization,she becomes a sexual object, strongly hyper‐sexualised and a usurper of power, which also partly constitutes genderidentity in Western culture.
Keywords: Schmidt, Martz, -- 1922-1998; Pérez Navarro, Francisco, -- 1953-; Cleopatra -- VII, -- Reina de Egipto; Cómics